2015
DOI: 10.3892/ijmm.2015.2066
|View full text |Cite
|
Sign up to set email alerts
|

Massive bowel resection upregulates the intestinal mRNA expression levels of cellular retinol-binding protein II and apolipoprotein A-IV and alters the intestinal vitamin A status in rats

Abstract: Abstract. Short bowel (SB) syndrome causes the malabsorption of various nutrients. Among these, vitamin A is important for a number of physiological activities. Vitamin A is absorbed by epithelial cells of the small intestine and is discharged into the lymphatic vessels as a component of chylomicrons and is delivered to the liver. In the present study, we used a rat model of SB syndrome in order to assess its effects on the expression of genes associated with the absorption, transport and metabolism of vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(27 reference statements)
0
8
1
Order By: Relevance
“…Increased Apoa4 and Rbp2 expression following SBR has been previously described 21, 22, 23. Contrary to our findings, one of these studies reported no significant changes in ileal Fabp1 mRNA expression.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Increased Apoa4 and Rbp2 expression following SBR has been previously described 21, 22, 23. Contrary to our findings, one of these studies reported no significant changes in ileal Fabp1 mRNA expression.…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to our findings, one of these studies reported no significant changes in ileal Fabp1 mRNA expression. However, this study examined whole tissue preparations, rather than epithelium at single-cell resolution 23 . Thus, to validate the transcriptional changes revealed by our scRNA-seq analysis, we surveyed Fabp1 expression via RNA fluorescence in situ hybridization (RNA-FISH) on histological sections of sham and SBR animals at 7 and 70 days postsurgery, with the latter analysis designed to investigate whether the observed changes are stable, a property rarely investigated in the context of SBR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, one of these studies reported no significant changes in ileal Fabp1 mRNA expression. However, this study examined whole tissue preparations, rather than epithelium at single-cell resolution 23 To further validate our findings, we performed quantitative immunofluorescence, western blotting, and qPCR for selected proteins and transcripts, including FABP1, FABP6, APOC3, Rbp2, and…”
Section: Regional Reprogramming Of Distal Si After Sbr Is Accompaniedmentioning
confidence: 89%
“…Retinol-binding protein transports vitamin A from the liver to other tissues like the intestine (47). It has been reported that tissue injury during inflammation causes a reduction in the synthesis of retinol-binding protein (48).…”
Section: Soy Products Evoked Inflammation-associated Signals In the Imentioning
confidence: 99%